Conceptualizing Responsibility in Food Research and Innovation to Promote Healthy and Sustainable Food Systems - Timotijevic, Lada; Hodgkins, Charo Elena; Peacock, Matthew; Raats, Monique Maria (Frontiers in Sustainable Food Systems, 2021)
Responsibility is crucial to governance and key to achieving legitimacy within complex systems, yet there is limited attention to how it should be conceptualized within the context of food research and innovation (R&I). Understanding how diverse stakeholders in food R&I conceptualize responsibility is vital because it shapes the way problems are identified, goals are set and solutions are put in place. We report on empirical research with diverse stakeholders across Europe to understand and map the dimensions of responsibility for food R&I to support healthy and sustainable food systems. Semi-structured interviews were conducted with 32 stakeholders working in R&I in the cutting-edge domains of: cultured meat as a substitute for livestock meat; new crop breeding of potatoes; and a new approach to obesity reduction that focuses on weight acceptance. Drawing from the empirical evidence collected, we developed a classification system that reflects various conceptualizations of stakeholders' responsibility for food R&I to support healthy and sustainable food systems. Our thematic analysis revealed four overlapping rationales of responsibility—accountability, impact, reflexivity, and responsiveness, and characterized them in terms of: who the researcher is responsible to; whether the assessments of responsibility focus on R&I processes or impact; whether responsibility implies societal engagement; and how responsibility is assessed—retrospectively or prospectively. The article provides a basis for systematic application of these criteria to the specific instances of food R&I governance and for future joint decisions, about the ways to allocate responsibilities.